Cyber resilience in industrial networks: A state of the art, challenges, and future directions - Thuraya N.I. Alrumaih; Mohammed J.F. Alenazi; Nouf A. AlSowaygh; Abdulmalik A. Humayed; Ibtihal A. Alablani (Journal of King Saud University: Computer and Information Sciences, 2023)
Industrial networks, and more particularly, industrial control systems (ICSs) and industrial Internet of things (IIoT), are no longer isolated environments. The rapid increase of functional needs in Industry 4.0 has indeed exposed them to numerous cyberattacks. Cyberattacks against ICSs or IIoT can cause considerable societal and economic disruption. Cyber resilient and cybersecurity practices are essential to integrate secure networks, control systems, physical processes, and their interconnections toward handling cyberattacks. In this paper, we survey relevant cyber resilience strategies for industrial networks, focusing on ICSs and IIoT. First, we provide a coverage of resilient networks and the fundamental components of ICSs and IIoT. Second, state of the art articles that propose cyber resilience assessment frameworks are reviewed. They are classified according to the resilience aspects they address and the defense mechanism, anomaly detection, failure management and survivability strategy, as well as resilience measure they present. As a result, the main technical and human related challenges, practical limitations, and current cyber resilience needs of industrial networks are identified. Finally, we establish the principal requirements that cyber resilience schemes for industrial networks should meet shortly and suggest promising directions for future research.